Acid monophosphatase: an indicator of phosphorus mineralization or of microbial activity? A case study from the Brazilian cerrados - Renz, TE; Neufeldt, Henry; Ayarza, Miguel Angel; Silva, J.E. da; Zech, W. (International Center for Tropical Agriculture, 1999)
Plant production in the Brazilian savannas, also known as the Cerrados, is limited mainly by low P availability. In tropical soils, rich in sesquioxides, P supply of plants depends heavily on the transformation of organic P by phosphatase enzymes into HPO 4 2- and H 2 PO 4-. We examined two Oxisols-one clayey and one loamy-under different land uses for their potential acid monophosphatase activity (PAMA) and potential microbial activity. We measured dimethyl sulfoxide reduction, pH, total C and N, and NaOH-extractable organic and inorganic P. For all parameters other than pH, values were about twice as high in the clayey as in the loamy soil. Land use was found to strongly affect phosphatase activity, which was reduced by both cropping and reforestation. In the clayey soil, pastures seemed to have a positive effect on phosphatase activity. A change of continuous cropping to pasture resulted in a rapid recovery of phosphatase activity, microbial activity, and C and N levels. However, it retained the high inorganic P (Pi) levels found in fertilized crops. A comparison of phosphatase activity with microbial activity, total C and N, and P fractions showed that phosphatase was strongly related to microbial activity in the soil and therefore depended much more on soil organic matter than on soil P levels. We also found that, although PAMA is useful for indicating a soil`s P mineralization capacity, it does not indicate actual P mineralization rates. However, when combined with findings for microbial activity and Pi, it indicates the level of microbially available P, a lack of which probably implies strong competition between plants and microorganisms for this element.